Nomads of the Oghuz-Pecheneg Time of the Volga-Don Region According to Anthropology Data. - Mariya Balabanova (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The article presents the results of an anthropological study of the nomads of the Oghuz-Pecheneg period of the Volga-Don region, known from written and archaeological sources. Material and methods. To carry out the analysis, both published materials and new ones studied by the author were used. The craniological series included data on 55 skulls – 38 male and 17 female. The new material is represented by skulls obtained from excavations of cemeteries in the Volgograd region, for 23 skulls. The anthropological composition, intragroup structure, and ethnogenetic connections were determined by the methods of simple and multivariate statistics. Analysis and discussion. The arithmetic mean values of the male and female craniological series demonstrated a racially mixed Caucasoid-Mongoloid complex, components of which are determined in men by II and in women by both I and II principal components. In addition, in the male series I, the main component performs the function of size and demarcates the skulls with a massive and gracile structure of the brain and facial regions. The multiple discriminant analysis carried out in order to identify ethnogenetic connections showed the greatest similarity of a series of nomads of the Oghuz-Pecheneg period both with their predecessors, the population of the Khazar period, and with groups of Cuman and Golden Horde nomads. The Turkic origin of the study group demonstrates connections with the synchronous populations of Southern Siberia and Kazakhstan. Conclusions. The Oghuz-Pecheneg people exhibited a racially heterogeneous anthropological composition, combining Mongoloid and Caucasoid components. This is a direct consequence of their origin. Apparently, the nomads of the Volga-Don region of the studied time, after its development, could include in their composition the nomadic groups of the previous Khazar time and form the composition of both the urban and nomadic population of the Golden Horde.